TRANSLANGUAGING PRACTICES IN MULTILINGUAL LANGUAGE CLASSROOMS: BENEFITS, CHALLENGES, AND PEDAGOGICAL IMPLICATIONS FOR INCLUSIVE LEARNING - Munawar Munawar; Kristina Gita Permatasari (SENSEI RESEARCH CENTER, 2025)
In Indonesia the students usually have more than one language, such as the local language, Indonesian, and English. In the classroom the teacher often mixes the languages so that the students can understand the lesson. This is called translanguaging. This study discusses translanguaging practices in multilingual classrooms. The study used a qualitative method with observation, interview, and document analysis in several classrooms. The result shows that translanguaging is often used by the teachers and it has many benefits, for example the students become easier to understand and more brave to speak. But there are also some challenges, for example the students become too dependent on their first language. Therefore, translanguaging should be used wisely by the teachers.